Visualizing the organization and reorganization of transcription complexes for gene expression. (22nd July 2008) - Burrows, Patricia C.; Wigneshweraraj, Sivaramesh; Bose, Dan; Joly, Nicolas; Schumacher, Jörg; Rappas, Mathieu; Pape, Tilmann; Stockley, Peter G.; Zhang, Xiaodong; Buck, Martin
Abstract : Regulated gene expression requires control of the transcription machinery, frequently through the establishment of different functional states of the transcribing enzyme RNA polymerase and its attendant activator proteins. In bacteria, major adaptive responses use an enhancer-dependent RNA polymerase, activated for transcription by a class of ATPases that remodel initial promoter complexes to form transcriptionally proficient open promoter complexes. In the present article, we summarize the integrated use of site-specific protein cleavage and DNA cross-linking methods, as well as FRET (fluorescence resonance energy transfer) in combination with X-ray crystallography and cryo-electron microscopy to gain insight into the organization of the enhancer-dependent σ 54 –RNA polymerase and the ATPase-driven activation mechanism.